Knowledge Management Components and its effect on Organizational Performance - Shah, Ghulam Murtaza; Yaseen, Ghazala Tunio; Memon, Noor Ahmed (Journal of Development and Social Sciences, 2025)
The main objective of this research is to investigate the effect of knowledge management components on organizational performance of commercial banks in hyderabad Sindh. Recognizing knowledge as a valuable asset the research focuses on organizations invested in knowledge management components which substantially improved organizational performance. Using quantitative research approach, structured survey method is used to collect primary data. Target population was managerial staff working in commercial banks and one hundred questionnaires were distributed among different managerial cadres. Data was analyzed using composite reliability, Average variance extracted, Fornell Larcker criterion for discriminant validity, Standardized root mean square residual and Normed Fit index for model fitness and Beta, P value and T statistics for Hypotheses testing. All components of knowledge management have significant effect on organizational performance. This research is guiding tool for financial institutes looking for better organizational performances because knowledge management is a fuel of right decision making.Knowledge Management